EXPERIMENTAL VERIFICATION OF EFFECTIVENESS OF TAKING PART IN ADDITIONAL MOTOR ACTIVITIES IN CONNECTION WITH FEMALE ABILITY - Y. Zlatarova (Trakia Journal of Sciences)
Achieving a health effect in sports activities within the Higher school is possible by applying a variety of targeted means and methods. The relevance of the study: Obtaining data on the impact of additional cyclic activity and gradual inclusion of exercises for general strength and resistance to the working capacity of students within the training process. Purpose of the study: Study of the reaction of the cardiovascular system and the achievements of female students after application of additional complexes of exercises in the syllabus of callanetics. At the beginning and at the end of the summer semester of 2018/2019 the female students were subjected to a 5-minute stepwise load of the cross trainer with a measurement of the frequency of cardiac contractions of the first, third and fifth minutes and the distance travelled distance of each of the three loading steps. For the realization of the research project a series of exercises with cyclic aerobic focus as well as static and dynamic strength exercises without and with aggravated. The applied exercises enhance the functional capabilities of the cardiovascular system and the level of total endurance and performance.